Pengembangan Modul Ajar Berbasis Pembelajaran Berdiferensiasi Pada Materi Perilaku Konsumen Kelaas X Bisnis Digital SMKS Ketintang SUrabaya - Robbih, Muhammad Nashiruddin Ibn Abdi; Sudarwanto, Tri (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
Abstract The change of the education curriculum in Indonesia to an independent curriculum requires adaptation in various aspects of learning activities, such as in terms of using teaching modules and learning strategies that are relevant and in accordance with the curriculum used. This study aims to develop and assess the quality of teaching modules and improve student learning outcomes, using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research subjects were students of class X Digital Business 2 SMKS Ketintang Surabaya. The research instruments included interviews, expert review and validation, student responses, and product effectiveness tests. Data analysis was carried out descriptively qualitative and quantitative. The results of the research are in the form of teaching modules based on differentiated learning with consumer behavior material in Marketing Basics subjects. The feasibility of the product was assessed as very feasible by material experts (83%), media (82%), and language (100%). The limited trial scored 87.37% (very feasible) and the large group trial 92.59% (very feasible). Product effectiveness showed a value of 0.78, with high effectiveness criteria. The teaching module developed can be used in the learning process.